Transformation of Labor Markets of the Southern Caucasus Countries in New Geopolitical and Economic Conditions - Ryazantsev, Sergey V.; Lukyanets, Artem S. (International Journal of Economics and Financial Issues, 2016)
The paper considers key issues of the labor market condition and operation in such Southern Caucasus countries as Armenia, Azerbaijan and Georgia. It has revealed the peculiarities of labor forces formation and the structure of their allocation. It has also fixed general peculiarities and significant distinctions in operation and tendencies of development. So, the paper sets significant influence of international labor migration to labor markets of the Southern Caucasus that exerts influence starting from the collapse of the USSR. The high level of self-employment of the population is a uniting element of the whole labor market of the Southern Caucasus countries. One more element of similarity of labor markets of the considered countries is the considerable specific weight of unpaid employees of family business concentrated in agriculture and services industry. At the same time, certain political events in some countries of the Southern Caucasus have mostly changed the labor market structure. Color revolutions which took place in some former countries of the USSR, besides the political line of policy, have also changed an economic vector of development. Rose Revolution, happened in 2003 in Georgia, has cardinally changed both domestic and international policies of the country. Orientation to closer integration with the western countries and military-political blocks predetermined the main strategy of development of the country that was inevitably reflected both political and economic ties with Russia. Because of fears concerning radical opposition formation the leadership of Armenia on the contrary was targeted to closer integration with Russia that greatly affected the labor market. Azerbaijani self-sufficiency in natural raw material resources, first of all, in oil with support of Turkey, allow the leaders of this country to conduct own policy without reference to some one country or integration group. Keywords: Southern Caucasus, Armenia, Azerbaijan, Georgia, labor market, employment, unemployment, economic development JEL Classifications: E20, E29, F63